PENERAPAN METODE GENETIK PADA SISTEM INFORMASI PENJADWALAN PERKULIAHAN STMIK JAKARTA STI&K - Linda Wahyu Widiyanti; Suyatno Suyatno (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
Lecture activities from a university are increasingly complex along with the number of scientific fields in a study program. One of these complications is the scheduling of courses given to students and supporting lecturers. The number of courses and the large number of lecturers make the scheduling process require extra in managing it. STMIK Jakarta STI&K is a college in the field of computers that has several study programs in the field of computers consisting of the Information Systems Study Program, Computer Systems and Information Management. At the beginning of each lecture, they often experience difficulties in scheduling the lectures. The need for a system that can process scheduling data is very important so that it can help maximize the process so that lecture activities are more organized. Answering the problem of the complicated process of scheduling lectures for students and lecturers, in this study a scheduling system was developed using the Genetic Method. The use of this genetic method can minimize scheduling conflicts between courses, between lecturers and between classes. The development of this scheduling system was developed using the PHP language and MySQL database so that it can be applied online so that the results can be directly informed to lecturers and students. Based on the application of the system developed, it helps the scheduling department of STMIK Jakarta STI&K faster in making schedules because it minimizes schedule conflicts, informs schedules more quickly so that all lecturers and students are better prepared. The comparison of the average speed of making schedules manually and using genetic methods is between 69.67 and 69.72.